2007
DOI: 10.1109/led.2007.895446
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Localization of the SiGe Source/Drain (S/D) Strain-Induced Defects in PMOSFET With 45-nm CMOS Technology

Abstract: In this letter, for the first time, the defects that are induced from the SiGe strain source/drain (S/D) in PMOSFET with 45-nm CMOS technology were investigated in detail. With the conventional charge pumping and the improved low gate-leakage gated-diode (L 2 -GD) measurements, we find that the uniaxial compressive stress from SiGe S/D generates a large number of acceptorlike interface states at the gate oxide/extension of S/D interface, thus enhancing the leakage current. Compared to defects that are caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…87 Such a possibility is analogous to the well-known phenomenon of stresses induced in a transistor which has SiGe source and drain regions. 88 However, during ion irradiation, the ␣-Si is subject to viscous flow [89][90][91] which could presumably allow for accommodation of the volumetric expansion and minimal resulting substrate stresses in patterned material. Thus, the possibility of stresses in the crystalline phase existing as a result of the amorphization process in patterned material needs further investigation but for purposes of clarity has not been addressed here.…”
Section: ͑10͒mentioning
confidence: 99%
“…87 Such a possibility is analogous to the well-known phenomenon of stresses induced in a transistor which has SiGe source and drain regions. 88 However, during ion irradiation, the ␣-Si is subject to viscous flow [89][90][91] which could presumably allow for accommodation of the volumetric expansion and minimal resulting substrate stresses in patterned material. Thus, the possibility of stresses in the crystalline phase existing as a result of the amorphization process in patterned material needs further investigation but for purposes of clarity has not been addressed here.…”
Section: ͑10͒mentioning
confidence: 99%
“…First, as compared with control device, the reduced LS VG level of the embedded SiGe S/D device implies the reduction of or . However, previous literature had reported that SiGe S/D process may lead higher [20,21]. In other words, it can only be assumed that the reduced mainly contributed to the decreased LS VG of SiGe S/D device.…”
Section: Resultsmentioning
confidence: 93%
“…Generally, epitaxial SiGe layer, where atomically Ge contents induce the film-strain, has been suggested for the sub-0.1 μm high speed and low-power CMOS [3]. Although the epitaxial SiGe is believed to be "compatible" to the processing of Si wafer based CMOS, it is hard to be realize in the large-scaled flat-panel display applications because the SiGe has to be fabricated in polycrystalline texture, which demonstrates a different complexion on the electric performance, not epitaxial film [4].…”
Section: Introductionmentioning
confidence: 99%